2017
DOI: 10.1111/bjd.15950
|View full text |Cite
|
Sign up to set email alerts
|

Research gaps in the management and prevention of cutaneous squamous cell carcinoma in organ transplant recipients

Abstract: Summary Although tremendous progress has been made in recent years in skin cancer care for organ transplant recipients, significant gaps remain in data-driven clinical guidelines, particularly for the treatment and prevention of cutaneous squamous cell carcinoma (cSCC), the most common malignancy among this population. In this review, we aim to summarize current knowledge around the management of cSCC and highlight the most significant gaps in knowledge that continue to pose challenges in the delivery of skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 68 publications
0
36
1
Order By: Relevance
“…We adjusted for several variables known to impact KC risk including exposure to azathioprine and HLA mismatch. Certain immunosuppressive agents, such as azathioprine, increase SCC risk by inducing DNA damage from accumulated 6-thioguanine (Blomberg et al, 2017;Jiyad et al, 2016;Perrett et al, 2008). In addition, a recent study reported that HLA mismatch was associated with reductions in the risk of skin cancer after solid-organ transplant, possibly because HLA mismatch activates immune surveillance mechanisms (Gao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We adjusted for several variables known to impact KC risk including exposure to azathioprine and HLA mismatch. Certain immunosuppressive agents, such as azathioprine, increase SCC risk by inducing DNA damage from accumulated 6-thioguanine (Blomberg et al, 2017;Jiyad et al, 2016;Perrett et al, 2008). In addition, a recent study reported that HLA mismatch was associated with reductions in the risk of skin cancer after solid-organ transplant, possibly because HLA mismatch activates immune surveillance mechanisms (Gao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained information on potential risk factors from Partners Research Patient Database Registry, including age at renal transplant, sex, comorbidities, chronological year of renal transplant to account for time trends in renal treatment regimens for both induction and maintenance, history of KC (defined as a previous diagnosis of either SCC or BCC before kidney transplant), type of transplant (i.e., kidney only vs. cotransplant [kidney and lung, heart, or liver]) to account for the potential differences in immunosuppression between single versus multiple organ transplant recipients, and the type of immunosuppression (e.g., calcineurin inhibitors [cyclosporine and tacrolimus], mTOR inhibitors [sirolimus and everolimus], mycophenolate mofetil [cellcept], and azathioprine [imuran]). Immunosuppression type was further categorized by azathioprine versus other immunosuppression, given that azathioprine has been associated with a higher risk of SCC (Blomberg et al, 2017). To account for the effect of HLA mismatch on the association between HLA type and incident KC risk, we captured the serological HLA type of the donor and recipient to account for the second field from the molecular typing.…”
Section: Covariate Assessmentmentioning
confidence: 99%
“…); and current research priorities (Blomberg et al .) . Although advances have been made, there remain important evidence gaps that are limiting development of more effective treatment and prevention strategies for cSCC in OTRs.…”
mentioning
confidence: 99%
“…Progress has been made in recent years in OTR cSCC treatment, prevention, screening and surveillance, but there remain significant uncertainties. Blomberg et al . summarize current knowledge in this area and highlight those research gaps of particular significance in better informing delivery of skin cancer care to OTRs.…”
mentioning
confidence: 99%
See 1 more Smart Citation